Two Cases of Direct Ethanol Injection Therapy for Hemangioma in the Oral and Maxillofacial Region - Amagasa, Teruo; Suzuki, Emina; Ishikawa, Hitoshi; Yamashiro, Masashi; Satou, Yutaka; Hasegawa, Kazuki; Miyamoto, Hideo (Journal of Japanese Society of Oral Oncology, 2005)
The selection of treatment is difficult in cases with hemangioma in the oral and maxillofacial region, in the order to preserve the preoperative function and esthetics of the organs. We planned to treat two cases of hemangioma in the tongue, lower lip and buccal mucosa with direct ethanol injection therapy. As these two cases were classified as lowflow type by hemangioma preoperative Dynamic MRI, we decided to treat these two cases with direct ethanol injecttion therapy. We achieved the reduction or disappear ance of the tumor without any functional or esthetic disorders.